2007
DOI: 10.1021/jp075861+
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of the Pyrolysis of Phenethyl Phenyl Ether:  Computational Prediction of α/β-Selectivities

Abstract: We calculated an overall alpha/beta-selectivity for the pyrolysis of phenethyl phenyl ether as a composite of the alpha/beta-selectivities in the hydrogen abstraction reactions by the phenoxyl and by the benzyl radical that is in excellent agreement with experiment. The difference between the individual selectivities for these radicals is explained by analyzing the electronic structure of the transition states. Spin delocalization of the single electron favors the alpha-pathways. An opposing effect occurs for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(118 citation statements)
references
References 54 publications
(88 reference statements)
9
107
1
Order By: Relevance
“…1 Thermogravimetric analysis of milled wood lignin isolated from Japanese cedar (Cryptmeria japonica) [9] understanding the pyrolytic reactions of lignins. Hence, various model dimers including β-ether [20,27,28,34,[40][41][42][43][44][45][46][47][48][49][50][51][52][53], α-ether [20,30,34,45,47,49,51,54], β-aryl [20,31,32,47,54], β-β [33], and biphenyl [20,47,54] types, trimers [34,49,51] and oligomers/polymers such as dehydrogenative polymerization products of cinnamyl alcohols [35] and β-ether type polymers [55][56][57] have been used in pyrolysis studies. Phenolic (Ph) and non-phenolic (Non-Ph) model compounds are commonly used to represent the ends and repeating units of lignin macromolecules, respectively.…”
Section: Primary Pyrolysis Reactions (200-400 °C)mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Thermogravimetric analysis of milled wood lignin isolated from Japanese cedar (Cryptmeria japonica) [9] understanding the pyrolytic reactions of lignins. Hence, various model dimers including β-ether [20,27,28,34,[40][41][42][43][44][45][46][47][48][49][50][51][52][53], α-ether [20,30,34,45,47,49,51,54], β-aryl [20,31,32,47,54], β-β [33], and biphenyl [20,47,54] types, trimers [34,49,51] and oligomers/polymers such as dehydrogenative polymerization products of cinnamyl alcohols [35] and β-ether type polymers [55][56][57] have been used in pyrolysis studies. Phenolic (Ph) and non-phenolic (Non-Ph) model compounds are commonly used to represent the ends and repeating units of lignin macromolecules, respectively.…”
Section: Primary Pyrolysis Reactions (200-400 °C)mentioning
confidence: 99%
“…The Brit and Beste research group have extensively studied hydrogen abstraction reactions from the C α − H bond and subsequent cleavage of the β-ether bond using phenethyl phenyl ether and its derivatives [43,44,46].…”
Section: Ether Cleavage Mechanismsmentioning
confidence: 99%
“…The approach was nested to allow simultaneous rotation around several bonds. The conformational space for the radical products was searched similarly, but with diffuse functions added to the 6-31G* basis set at the location(s) of the unpaired electron (designated in our papers as the MIXED basis [26,28,29] ). Second, the lowest energy conformers, as determined at M06-2X/6-311 + +G**//MIXED, were optimized at M06-2X//6-31 + +G**.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In our previous work, the MIXED basis was sufficient for geometry optimization. [26,29] However, given the presence of hydrogen bonds in the systems studied, we included polarization and diffuse functions on all atoms. DFT calculations of OÀH BDEs in ortho-substituted phenols showed an increase in accuracy when such functions were included.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Such carbonization studies will be conducted in future investigations, as shown in Fig. 18a and b [96][97][98][99][100][101][102][103][104][105][106][107][108][109].…”
Section: Sulfuric Systemmentioning
confidence: 99%